Conceptual Model of Supply Chain Resilience on Logistics Service Providers (People, Profit, Product and Planet) - Maryam Mufidah CHE SOBRY; Noorliza KARIA (Communications of International Proceedings, 2024)
Enhancing supply chain resilience amidst disruptions is increasingly vital, especially for Logistics Service Providers (LSPs) in Malaysia. This conceptual paper aims to present the process of developing a 4P Supply Chain Resilience Model using the Quadruple Bottom Line (QBL) approach, which encompasses People, Profit, Product, and Planet. This process includes theme analysis, critical literature review analysis and bibliometrics analysis. The purpose of this paper is to understand how the QBL framework can add value and enable resilience within logistics services. By examining the 4Ps, the paper aims to identify how each element contributes to resilience, providing insights into current practices and their implications for competitive advantage and firm performance. This framework offers a comprehensive view of how interconnected QBL factors can enhance organizational and supply chain resilience. It highlights the importance of integrating People, Profit, Product, and Planet into resilience strategies, offering a valuable tool for managers and policymakers to address risks and foster global networks.
Keywords: Supply Chain Resilience; Logistics Service Providers; Resilience